PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN TAPEN KABUPATEN BONDOWOSO - Afifah Afifah; Eddy Basuki; Farida Hanum (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2018)
This research aims to find out the effects of work discipline on employee’s performance in Tapen Subdistrict, Bondowoso Regency both partially and simultaneously. There were 30 respondents in this research.The sampling technique used in this research was saturated sampling technique which used the entire population as a sample. Data analysis in this study uses classical assumption test, t test, f test, multiple linear regression analysis and coefficient of determination with SPSS software version 23.0 for Windows as the software assistance. The results showed that the variable of work discipline as well as as thevariable of work environment had a positive and significant effects on employee’s performance.